2014
DOI: 10.1073/pnas.1321541111
|View full text |Cite
|
Sign up to set email alerts
|

Readily releasable vesicles recycle at the active zone of hippocampal synapses

Abstract: During the synaptic vesicle cycle, synaptic vesicles fuse with the plasma membrane and recycle for repeated exo/endocytic events. By using activity-dependent N-(3-triethylammoniumpropyl)-4-(4-(dibutylamino) styryl) pyridinium dibromide dye uptake combined with fast (<1 s) microwave-assisted fixation followed by photoconversion and ultrastructural 3D analysis, we tracked endocytic vesicles over time, "frame by frame." The first retrieved synaptic vesicles appeared 4 s after stimulation, and these endocytic vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…CIE of SV membranes has been observed at inner hair cell synapses from conditional AP-2 KO mice (Jung et al, 2015), cerebellar mossy fiber synapses (at least for low to moderate stimuli; Delvendahl et al, 2016), and in retinal bipolar neurons (Llobet et al, 2011). Moreover, our data are in good agreement with the observed formation of non-coated endocytic intermediates within 4-30 s in microwave-fixed electrically stimulated hippocampal neurons (Schikorski, 2014) and in photoreceptors (Fuchs et al, 2014). Finally, CIE of SVs is consistent with the surprisingly mild phenotypes of genetic KO of clathrin (Sato et al, 2009), AP-2 (Gu et al, 2008;Kononenko et al, 2014), AP180 (Koo et al, 2015), or stonin 2 (Kononenko et al, 2013) on the kinetics of SV retrieval in different organisms and systems.…”
Section: Discussionsupporting
confidence: 89%
“…CIE of SV membranes has been observed at inner hair cell synapses from conditional AP-2 KO mice (Jung et al, 2015), cerebellar mossy fiber synapses (at least for low to moderate stimuli; Delvendahl et al, 2016), and in retinal bipolar neurons (Llobet et al, 2011). Moreover, our data are in good agreement with the observed formation of non-coated endocytic intermediates within 4-30 s in microwave-fixed electrically stimulated hippocampal neurons (Schikorski, 2014) and in photoreceptors (Fuchs et al, 2014). Finally, CIE of SVs is consistent with the surprisingly mild phenotypes of genetic KO of clathrin (Sato et al, 2009), AP-2 (Gu et al, 2008;Kononenko et al, 2014), AP180 (Koo et al, 2015), or stonin 2 (Kononenko et al, 2013) on the kinetics of SV retrieval in different organisms and systems.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study showed that clathrin‐dependent endocytosis is essential for release sites clearance rather than vesicles reuse (Hua et al , ). Consistently, two studies indicated that SV recycling during moderate stimulation does not involve clathrin coat assembly (Watanabe et al , ; Schikorski, ), and a third study revealed that clathrin and AP‐2 are not essential for SV recycling (Kononenko et al , ). In particular, a newly described “ultrafast” endocytosis mechanism retrieves small endosome‐like structures from the plasma membrane in response to single APs (Watanabe et al , ), implying that additional sorting mechanisms would be necessary to maintain appropriately sized releasable SVs.…”
Section: Discussionmentioning
confidence: 79%
“…; Kononenko and Haucke ). Indeed, the rapidly recycling pool of SVs appears to utilize multiple endocytic modes following exocytosis (Schikorski ).…”
Section: Discussionmentioning
confidence: 99%